Implementasi Terapi Relaksasi Murottal Al-Qur'an Untuk Meningkatkan Kualitas Tidur Pada Pasien Lansia Dengan Insomnia - Salsabilla Salwa; Armi Mawaddah (STIKES Columbia Asia Medan, 2025)
Background: Insomnia is a common sleep disorder in the elderly, characterized by difficulty initiating or maintaining sleep, which negatively impacts quality of life. Data show a significant prevalence of insomnia in the elderly, including at the Malahayati Islamic Hospital in Medan. Non-pharmacological therapies, such as Quran recitation relaxation therapy, offer a promising alternative approach to addressing this problem.